Laparoscopic Repair of Bilateral Inguinal Hernia in Female - A Case Report - Mondal, Samiron Kumar; Roy, Sharmistha (Bangladesh Critical Care Journal, 2015)
Inguinal hernia is relatively uncommon in female, as compared to in males. The ratio of male to female is 6:11. The reason behind that is favorable stronger inguinal anatomy in females. This is a case of 59 years old lady presenting with pain in groin diagnosed as case of bilateral indirect inguinal hernia and was treated successfully by laparoscopic transabdominal pre-peritoneal (TAPP) hernioplasty Bangladesh Crit Care J September 2015; 3 (2): 79-80